Evaluation of the Diagnostic Performance of a Semiquantitative Cryptococcal Antigen Point-of-Care Assay among HIV-Infected Persons with Cryptococcal Meningitis - (:unkn) unknown (Journal of clinical microbiology, 2021)
A newly developed cryptococcal antigen (CrAg) semiquantitative (SQ) lateral flow assay (LFA) provides a semiquantitative result in a rapid one-step test instead of performing serial dilutions to determine CrAg titer. We prospectively compared the diagnostic performance of the CrAgSQ assay (IMMY) with the CrAg LFA (IMMY) on cerebrospinal fluid (CSF) samples collected from persons with HIV-associated meningitis. The CrAgSQ grades (1+ to 5+) were compared with CrAg LFA titers and quantitative CSF fungal cultures. Among 87 participants screened for HIV-associated meningitis, 60 had cryptococcal meningitis (59 CrAg positive [CrAg+] by LFA and 1 false negative due to prozone with CrAg LFA titer of 1:1,310,000 and culture positivity), and 27 had no cryptococcal meningitis by CrAg LFA or culture. The CrAgSQ on CSF had 100% (60/60) sensitivity and 100% specificity (27/27). CSF CrAg titers ranged from 1:5 to 1:42 million. CrAgSQ grades of 1+, 2+, 3+, 4+, and 5+ corresponded to median CrAg LFA titers of 1:<10, 1:60, 1:7,680, 1:81,920, and 1:1,474,000, respectively. CSF CrAgSQ grades 3+ or higher were always CSF culture positive. Mortality at 14 days for those with low CrAgSQ grade (1+ to 3+) was 5% (1/22) versus 21% (8/38) with high CrAgSQ grades (4+ to 5+) (P = 0.084). The CrAgSQ demonstrates excellent diagnostic performance, maintaining both the sensitivity and specificity of the CrAg LFA, and counters false-negative prozone effects. The CrAgSQ assay reading is more complex but does provide useful clinical information about disease burden and probability of culture positivity in a single rapid diagnostic test.